Differences in levels of the transmembrane protein Crumbs can influence cell survival at clonal boundaries. - Hafezi, Y.; Bosch, J.A.; Hariharan, I.K. (Developmental Biology, 2012)
The survival and growth of individual cells in a tissue can be nonautonomously regulated by the properties of adjacent cells. In mosaic Drosophila imaginal discs, for example, wild-type cells induce the elimination of adjacent slow-growing Minute cells by apoptosis, while, conversely, certain types of faster-growing cells are able to eliminate adjacent wild-type cells. This process, known as cell competition, represents one example of a diverse group of phenomena in which short-range heterotypic interactions result in the selective elimination of one type of cell by another. The mechanisms that designate "winner" and "loser" genotypes in these processes are not known. Here we show that apoptosis is observed preferentially at boundaries that separate populations of cells that express different levels of the transmembrane protein Crumbs (Crb). Cells that express higher levels of Crb tend to be eliminated when they are near cells that express lower levels of Crb. We also observe distortions in the structure of epithelia on either side of boundaries between populations of cells that differ in Crb expression. Thus, while previous studies have focused mostly on the cell autonomous functions of Crb, we show that Crb can regulate cell survival and tissue morphology nonautonomously. Moreover, we find that the extracellular domain (ECD) of Crb, which seems to be dispensable for some of the other characterised functions of Crb, is required to elicit the nonautonomous effects on cell survival. The ECD can also regulate the subcellular localisation of Hippo pathway components, and possibly other proteins, in adjacent cells and may therefore directly mediate these effects. Several genetic lesions alter Crb levels, including loss-of-function mutations in hyperplastic tumour suppressors in the Hippo-Salvador-Warts pathway and in neoplastic tumour suppressor genes, such as scribble. Thus, Crb may be part of a "surveillance mechanism" that is responsible for the cell death that is observed at the boundaries of mutant clones in these cases.